Evaluation of the Productive Zakat Program of BAZNAS: A Case Study from Western Indonesia - Mohamad Soleh Nurzaman; Ninik Annisa; Ridho Gusti Hendharto; Khairunnajah ,; Noviyanti , (International Journal of Zakat, 2017)
This paper aims to measure the impact of zakat distribution program implemented by Indonesia’s National Zakat Board (BAZNAS). The study intended to accurately assess the impact of the program for a potential extension to other zakat institutions. The studyadopted theCIBEST model developed by Beik and Arsyianti (2015), a quadrant model that combines the fulfillment of human needs that are both material and spiritual. The CIBEST consists of well-being index, material poverty index, spiritual poverty index, and absolute poverty index. The study has found that fund distribution by BAZNAS through the productive zakat program is quite effective in improving the welfare index of mustahik households in both material and spiritual aspects. Keywords: CIBEST model, Mustahik, Productive Zakat